A multidisciplinary perspective on the relationship between sustainable built environment and user perception: a bibliometric analysis - Ye, Yang; Huang, Yi; Li, Shuqi (Frontiers in Built Environment, 2023)
The study of the relationship between sustainable built environment and user perception involves multiple disciplines. Previous research has often taken a single perspective, displaying neither a holistic view of the relationship nor a systematic and refined grasp of the research content. This has resulted in a biased understanding of the two research objects and their respective measurement methods and made it difficult to develop synergies. In this context, this paper summarises the current research hotspots and trends in the relationship between sustainable built environment and user perception through CiteSpace quantitative analyses such as keyword co-occurrence networks, emergent word detection, and disciplinary re-clustering, and takes a multidisciplinary perspective to focus on relevant research in public health, environmental science, and architecture and urban design, such as the progress of research between sustainable built environment and users in physical activity, environmental cognition, and image perception. The results show that in the environmental science field, environmental cognition is the core, based on the study of users' direct perception of sustainable built environment and its externalisation in the expression of behaviours. The public health field and the architecture and urban design field are dominated by the study of perceptual outcomes. There is a trend towards big data as a measurement tool for research subjects in all fields.The study provides a framework for research into the relationship between the two from a broader perspective and provides guidance for future multidisciplinary research, with implications for the construction of high-quality human-centred urban spatial environments.